What do we know about the future of the environment and biodiversity in relation to food systems? - Gotor, Elisabetta; Masso, Cargele (International Food Policy Research Institute, 2025)
The environment’s proper functioning is essential for a better life on Earth, including maintaining, enhancing, and restoring biodiversity and ecosystem services. While the environment is driven by external factors and shocks as well as interventions within the global food system, it simultaneously drives the overall health and stability of the planet. This relationship involves complex interactions and tipping points, which foresight research needs to capture in analyzing alternative future pathways for food system transformation.